2022
DOI: 10.3389/fpubh.2021.762370
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Cardiovascular Calcification and Its Prognostic Effects Among Patients With Chronic Kidney Disease: Results From the C-STRIDE Study

Abstract: Background and Aims: The purpose of this study was to identify the characteristics and risk factors for cardiovascular calcification, and its relationship to prognosis, in patients with chronic kidney disease (CKD) stages 1–4.Methods: Cardiovascular calcification was evaluated at baseline by lateral abdominal radiography to detect abdominal aortic calcifications (AAC), and by echocardiogram to detect cardiac valvular calcifications (CVC), respectively. Demographic and laboratory data were collected and analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…Following the inclusion criteria, 22 (12,(15)(16)(17)(18)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) articles were eventually included in our study. The study selection process is depicted in Figure 1.…”
Section: Baseline Characteristics Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the inclusion criteria, 22 (12,(15)(16)(17)(18)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) articles were eventually included in our study. The study selection process is depicted in Figure 1.…”
Section: Baseline Characteristics Of the Included Studiesmentioning
confidence: 99%
“…The study selection process is depicted in Figure 1. Among those including articles, 13 studies only reported associated factors for development of CVC, while the other 9 (15)(16)(17)(18)(38)(39)(40)(41)(42) studies also explored the association of CVC and mortality meanwhile. Patients treated with hemodialysis were enrolled in 9 studies, while patients treated with peritoneal dialysis were enrolled in 6 studies.…”
Section: Baseline Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The abdominal aortic calcification score correlated significantly with calcification of the aortic valve and mitral annulus in prevalent HD patients [ 24 ]. The C-STRIDE study analyses showed that AAC may be associated with the risk of death for patients with CKD of any severity, while CVC is a possible risk factor for cardiovascular disease but only among those patients with mild to moderate CKD in the Chinese cohort [ 25 ]. Our previous study found that CVC increased the risk of all-cause and cardiovascular mortality among HD patients [ 26 ].…”
Section: Discussionmentioning
confidence: 99%